THE USE OF GENETIC BUTTON MEDIA IN IMPROVING BIOLOGY LEARNING ACHIEVEMENT OF CLASS XII SCIENCE STUDENTS OF SMA NW MATARAM WITH THE LEARNING MODEL OF THE STUDENT TEAM-ACHIEVEMENT GROUP FOR THE 2019-2020 ACADEMIC YEAR - mahnep mahnep (Jurnal Inovasi Pendidikan dan Sains, 2022)
Based on the author's experience and observation that the biological learning process at SMA NW Mataram, generally still uses a classic approach pattern, teachers dominate the learning process with lecture methods, reading, doing tasks and training to answer questions. While students just sit, listen, take notes, memorized, and do problem exercises. So that the author tried alternatives in using media in the learning process, one of which is with genetic button media, namely learning by using tools in the form of objects that resemble buttons. This genetic button media is usually used in trait inheritance learning materials. In addition to using the media is also applied the learning model of the Student-Achievement Group Team, which is a cooperative learning model, which emphasizes group cooperation in understanding the material taught. Likewise with the results of observation assessments on teacher activities in learning. The use of media and learning models aims to improve student learning achievement and improve student understanding In this study who are the subject of research are students of SMA NW Mataram, class XII IPA semester V, school year 2019/2020. The results showed of student learning evaluation, the average test score in first cycle was 7.03 with a classical graduation percentage of 76.92%. Furthermore, the average test in second cycle is 6.43 with a classic graduation percentage of 78.57%. There was an increase in the percentage of graduations, while the average decreased. Next, the average value of the third cycle test is 6.74 with a classical graduation percentage of 85.71%, there is also an increase in accordance with the success indicator that is 85% for classical evaluation results. Likewise, the results of observation assessments on teacher activities in learning, in general showed excellent category results, reaching 78% in first cycle, 80.60% in second cycle and 86.10% in third cycle. Based on the results of this study, it can be concluded that the application of genetic button media with the student-achievement group team learning model, in biology learning can improve students' learning achievements and can improve students' understanding of basic competencies in biology subjects.